The Taylor series expansion coefficients for solutions of the Emden‐Fowler type equations - Gritsans, A.; Sadyrbaev, F. (Mathematical Modelling and Analysis, 2005)
We present the explicit non‐recursive formulas for the Taylor series expansion coefficients for the functions Sn (t) defined as solutions of the Emden ‐ Fowler type equations x” = –nx 2n−1 with the initial conditions x(0) = 0, x‘(0) = 1, where n = 1,2,…Emdeno-Flauerio tipo lygčių sprendinių dėstinių Teiloro eilutėmis koeficientaiPateikiamos vadinamos Emdeno‐Faulerio lygties x” = –nx 2n−1 pradinio uždavinio x(0) = 0, x‘(0) = 1,(n = 1,2,…) sprendinių Sn (t) Teiloro eilutė koeficientų išreikštinės formulės. Jos yra nerekursyvinė.First Published Online: 14 Oct 2010